ARTS AND FOLKLOR OF LAYANG MUSEUMSAS ONE OF THE CULTURAL TOURISM DESTINATIONS AND EDUCATION IN JAKARTA - Priyanto, Priyanto (UI Scholars Hub, 2020)
There are quite a lot of cultural and educational destinations in Jakarta. One of them is the Jakarta Kite Museum (MLJ) Arts and Folklore. MLJ has a significant task, namely preserving and developing the kite culture, which does not only come from various regions in Indonesia but also from abroad. MLJ has a lot of potential to be further developed as a cultural and educational tourism destination. However, the potential that is owned, such as the number of kite collections that reach 600 san of various unique shapes and sizes as well as several MLJ programs have not been fully developed. The purpose of this study was to examine MLJ folklore and arts as a cultural and educational tourism destination. This research method uses a qualitative research approach with descriptive analysis. The stages of the research are observation, description and interpretation through the folklore art concept approach, cultural tourism concept and museum concept (museology). The results obtained show that MLJ has unique advantages including the attractiveness of collections of various shapes, types and sizes that are presented through the museum activity program and can be one of the attractions of cultural and educational tourism destinations that are beneficial to the community.